we'll introduce some theorems later used. i won't give full proof for below theorems but some basic ideas. readers are welcomed to prove for his own.
theorem A : Γ⊢φ iff Γ∪Λ tautologically implies φ.
proof
for (→), use induction for all i<k at deduction sequence <a1,…,an> where an=φ theorem of Γ. for ak, use induction principle(2 cases. φ∈Γ∪Λ and φ is obtained by modus ponens).
for (←), use compactness theorem for sentential logic(second version). then you can get tautology and by using modus ponens finitely, you can get deduction of φ from Γ
Generalization theorem : let Γ⊢φ and x does not occur free in any formula in Γ. then Γ⊢∀xφ.
proof
define S={φ|Γ⊢∀xφ} where φ is any theorem of Γ. use induction principle introduced at FOL(3). then you can get the result that every theorem φ of Γ belongs to S.
Rule T : if Γ⊢α1, …, Γ⊢αn and {α1,…,αn}⊨β, Γ⊢β.
proof : α1→α2→…→αn→β is tautology. now use modus ponens at deduction from Γ where an for all n∈N is enumerated.
Deduction theorem : if Γ;γ⊢φ, then Γ⊢(γ→φ).
proof : use theorem A. the converse part can be got from modus ponens(for this, you've to check if Γ1⊢φ, then Γ2⊢φ where Γ1⊆Γ2, which is trivial from definition of 'deduction'. rigorously, use induction for deduction sequence)
Contraposition theorem : if Γ;φ⊢¬ψ, then Γ;ψ⊢¬φ.
proof : use rule T and deduction theorem.
reduction to absurdity(reductio ad absurdum, RAA) : if Γ;φ is inconsistent, then Γ⊢¬φ.
(*Γ is inconsistent iff Γ⊢β and Γ⊢¬β for some β)
proof : use definition of inconsistent, deduction theorem, and rule T. actually, antecedent and consequent of RAA is equivalent if you konw 'if Γ1⊢φ, then Γ2⊢φ where Γ1⊆Γ2'.
Generalization on constants : Assume that Γ⊢φ and that c is a constant symbol that does not occur in Γ. Then there is a variable y (which does not occur in φ) such that Γ⊢∀yφcy. Furthermore, there is a deduction of ∀yφcy from Γ in which c does not occur.
(*φcy is a result of replacing c to y)
proof
part 1 : consider deduction sequence of φ from Γ. <a1,…,an> where an=φ. verify <a1cy,…,ancy> is a deduction from Γ using defintion of deduction(use strong induction for all i<k)(you can find y for any variable that does not occur in deduction sequence). then we get Γ⊢φcy.
part 2 : consider Φ⊆Γ finite set which is used for deducing φcy. then trivially Φ⊢φcy. then y does not occur in Φ(consider the case ak∈Γ. then you can understand y does not occur in ak by assumption. and since c does not occur in ak, (ak)cy=ak). then by generalization theorem, Φ⊢∀yφcy. thus Γ⊢∀yφcy.
Theorem B : Assume that Γ⊢φxc , where the constant symbol c does not either occur in Γ or in φ. Then Γ⊢∀xφ, and there is a deduction of ∀xφ from Γ in which c does not occur.
proof : use generalization theorem and axiom group 2 and re-replacement lemma.
(* re-replacement lemma : if y does not occur in φ, then x is substitutable for y in φyx and (φxy)yx=φ)(for this, use induction for formulas)
Rule EI : let c does not occur in φ,ψ,Γ and Γ;φxc⊢ψ. then Γ;∃φ⊢ψ.
proof : use contraposition theorem and rule T(or use tautology that (α→β)→(¬β→¬α). also use theorem B.
alphabetic variants theorem : let φ be any formula, t a term, x a variable. then there exists φ′ such that φ⊢φ′ and φ′⊢φ, and t is substitutable for x in φ′.
proof : use induction for formulas. for atomic, φ′=φ. and each case, take (¬φ)′=¬φ′, (φ→ψ)′=φ′→ψ′. but situation differs about ∀yφ. in this case, take (∀yφ)′=∀z(φ′)yz. and divide cases into x does not occur free, and x does occur free in φ′ where t is substitutable for x in φ′ by inductive hypothesis. the intuitive idea for quantifier is like this;
suppose we want to have 'y is substitutable for x' in ∀yPxy for getting axiom group2 formula ⊢∀x∀yPxy→∀yPyy. but this always fails. to get this, we can change some variables in ∀x∀yPxy like ∀x∀zPxz where they are deducible from each other. then clearly y is substitutable for x in ∀x∀zPxz we've taken and thus ⊢∀x∀zPxz→∀yPyy. thus if you can calculate ⊢∀x∀yPxy→∀x∀zPxz, original formula can be proved.
Equality theorem(equivalence relation of '=')
(i) '=' is reflexive : ⊢x=x
(ii) '=' is symmetric : ⊢x=y→y=x
proof
⊢x=x→(x=x→x=y) by axiom group6
⊢x=x→x=y since x=x is in axiom group5 & using rule T
(iii) '=' is transitive : ⊢x=y→y=z→x=z
proof
⊢y=x→y=z→x=z by axiom group5
then x=y⊢y=x thus x=y⊢y=z→x=z. hence,
⊢x=y→y=z→x=z by deduction theorem.
using generaliation theorem on (i), (ii), (iii), we get
⊢∀xx=x
⊢∀x∀yx=y→y=x
⊢∀x∀y∀zx=y→y=z→x=z
'학문 > 수리논리학' 카테고리의 다른 글
FOL(6) - soundness theorem and its equivalence (0) | 2015.02.12 |
---|---|
FOL(5) - soundness theorem (1) | 2015.02.12 |
FOL(3) - syntax(1) (2) | 2015.02.11 |
FOL(2) - semantics (2) | 2015.02.10 |
completeness theorem for PL (2) | 2015.02.07 |